Fungicide resistance toward fludioxonil conferred by overexpression of the phosphatase gene MoPTP2 in Magnaporthe oryzae. Issue 3 (21st January 2019) - Bohnert, Stefan; Heck, Larissa; Gruber, Christoph; Neumann, Hendrik; Distler, Ute; Tenzer, Stefan; Yemelin, Alexander; Thines, Eckhard; Jacob, Stefan
Summary: The fungicide fludioxonil causes hyperactivation of the Hog1p MAPK within the high‐osmolarity glycerol signaling pathway essential for osmoregulation in pathogenic fungi. The molecular regulation of MoHog1p phosphorylation is not completely understood in pathogenic fungi. Thus, we identified and characterized the putative MoHog1p‐interacting phosphatase gene MoPTP2 in the filamentous rice pathogen Magnaporthe oryzae . We found overexpression of MoPTP2 conferred fludioxonil resistance in M. oryzae, whereas the 'loss of function' mutant ΔMoptp2 was more susceptible toward the fungicide. Additionally, quantitative phosphoproteome profiling of MoHog1p phosphorylation revealed lower phosphorylation levels of MoHog1p in the MoPtp2p overexpression mutant compared to the wild‐type strain, whereas MoHog1p phosphorylation increased in the ΔMoptp2 mutant. Furthermore, we identified a set of MoHog1p‐dependent genes regulated by the MoPtp2p expression level. Our results indicate that the phosphatase MoPtp2p is involved in the regulation of MoHog1p phosphorylation and that overexpression of the gene MoPTP2 is a novel molecular mechanism of fungicide resistance. Abstract : Elucidation of the molecular principles of fungicide resistance is of great importance in order to identify new antifungal drugs and understanding fungal physiology. In this study, we demonstrated for the first time that overexpression of the phosphatase MoPtp2p represents a novel molecular mechanism of fludioxonil resistance in a filamentous pathogen – the rice blast fungus Magnaporthe oryzae .